Penguatan Literasi Siswa SMP Negeri 2 Galesong Selatan Melalui Implementasi KKN Mahasiswa FKIP UNISMUH Makassar - Mustafa Herman; Ashar Reskiyawan; Abdul Wahid (Lembaga Pengembangan Kinerja Dosen, 2025)
This article explores the implementation of a Community Service Program (KKN) carried out by students from the Faculty of Teacher Training and Education at Unismuh Makassar with the objective of improving reading and writing skills among students at SMP Negeri 2 Galesong. The KKN activities were specifically designed to strengthen literacy development through various programs, including the cultivation of daily reading habits, the establishment of literacy corners in classrooms, and creative writing training aimed at encouraging students to express ideas in written form. This study employed a descriptive qualitative approach, with data collected through direct observation, interviews with teachers and students, and documentation of literacy activities. The results indicate a significant increase in students’ interest and motivation in reading activities, as well as more active participation during literacy sessions. In addition, students demonstrated improvement in the quality of simple written texts, particularly in terms of idea organization and expression. Overall, the implementation of the KKN program proved effective in supporting the development of a positive literacy culture and enhancing students’ basic literacy skills within the school environment.